Effect of integrated weed-management practices on yield and economics of babycorn (Zea mays) - PANDEY, A K; PRAKASH, VED; GUPTA, H S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the rainy (Kharif) season of 1999 and 2000 at Almora, Uttaranchal, to work out effective weed- management practices for babycorn (Zea mays L.) cultivation. Fourteen treatments, comprising atrazine @ 0.625 and 1.25 kg/ha, pendimenthalin @ 075 and 1.50 kg/ha, alachlor @ 1.00 and 2.00 kg/ha and lower levels of these hearbicides appled in combination with hand- weeding 3 days after sowing, hand-weeding 15 days after sowing alone andÂ  in combination with paraquat at 0.50 kg/ha (30 days after sowing) and earthing up (30 daus after sowing) were compared with weed-free and weedy checks. Season long weed infestation reduced the babycorn yield by 44.0%. All the weed-control treatments improved yield attributes and babaycorn and green fodder yield significantly and enhanced monetary returns compared wth weedy check. The highest babycorn (1. 253 tonnes/ha) and green fodder yield (28.2 tonnes/ha) were recorded under weed-free treatmen, followed by comparble yields recorded under hand weedingÂ  15 days after sowing intergrated with earthing up, pre-emergence herbicides at lower levels applied in combination with hand-weeding 30 days after sowing, and pendimethalin @ 1.50 kg/ha and alachlor@2.00 kg/ha alone. Remaining treatrnents recorded considerably lower yields compared with weed-free treatment. All the weed-control treatments recorded considerably higher returns over weedy check, which ranged from Rs 4 010 to Rs 15 576/ha. Highest additional return of Rs 15 576/ha Was recorded under pre-emergence alaehlor@ 1.00 kg/ha applied in integration with hand-weeding 30 days after sowing followed by its sole application @ 2.00 kg/ha. Despite highest yield, weed-free treatment recorded considerably lower auditional returns due to very high cost involved in treatment application.